Estudo das interações de peptídeos antimicrobianos e sistemas miméticos de membrana por dinâmica molecular - Baldissera, Gisele [UNESP] (2014)
Many peptides extracted from plants and animal secretions exhibit a broad spectrum of antimicrobial activity against bacteria gram-negative, gram-positive, fungi and parasites. Due this characteristic and the increasing resistance of pathogenic microorganisms to conventional forms of treatment, it is speculated the use of these peptides as potential new drugs. Therefore, various experimental and theoretical techniques that make use of membrane mimetic systems have been used to study the mechanisms of action of this class of peptides. In this work, we use molecular dynamics simulations to understand the influence of some characteristics of interaction peptide-peptide and peptide-membrane on biological efficiency of the Protonectins and Jelleines. Protonectin and Protonectin 1-6 are antimicrobial peptides, the first shows hemolytic activity, mast cell degranulation and chemotaxis, while the second presents chemotactic activity. Experimental data indicate that the association between those two peptides (1:1) generates a supramolecular aggregate structure and also increases the hemolytic and mast cell degranulation activities, while the chemotactic activity decreases, i.e., in combination they exhibit accentuated behavior of the interaction with membranes. Based on these results in this work, we speculate, which the interactions between Protonectin/Protonectin 1-6 (mixture) that would be associated with the formation of aggregate structure and the implications of this structure in the interaction with membrane mechanism. The results of the simulations in water and SDS micelle for these peptides indicate that there is a tendency of aggregation between pure Protonectins and Protonectin/Protonectin 1-6, and that this occurs through intermittent hydrogen bonds. Furthermore, it was found that the electrostatic interactions between the mixture of peptides is less favorable than for the pure Protonectins, influencing the distance between the ...